KEABSAHAN PEMBERHENTIAN HAKIM MAHKAMAH KONSTITUSI BERDASARKAN USULAN DEWAN PERWAKILAN RAKYAT - Moh. Syaihol Hadi (Fakultas Hukum Universitas Narotama, 2023)
This legal issue is case study on the dismissal of Aswanto’s Judge based on the recommendation of the House of Representative (DPR). The focus of this research is to analyze the issue of the legal status of dismissal and resulting legal consequences. Legal study of this case is analyzed from three perspective, namely the perspective of normative law, administrative law, constutional law. This is normative’s research through statute approach, case approach, and conceptual approach. The results of this research show that the dismissal Aswanto’s Judge is contrary to normative law, which is based on the UUD 1945 and Law on the Constitutional Court. However, the status of his dismissal remains legally and has legal force because it is bound by Presidential Decree (Keppres). Likewise, when referring to the doctrine of constitutional law, this practice can be called a constitutional convention. Keyword: Judge of Constitutional Court, Dismissal, House of Representative (DPR)